The story of food n illustrated history of everything we eat (Dorling Kindersley Limited, 2018)
"This glorious visual celebration of food in all its forms reveals the extraordinary cultural impact of the foods we eat, explores the early efforts of humans in their quest for sustenance, and tells the fascinating stories behind individual foods. With profiles of the most culturally and historically interesting foods of all types, from nuts and grains, fruits and vegetables, and meat and fish, to herbs and spices, this fascinating culinary historical reference provides the facts on all aspects of each food's unique story. Feature spreads shine a spotlight on influential international cuisines and the local foods that built them. The Story of Food explains how foods have become the cornerstone of our culture, from their origins to how they are eaten and their place in world cuisine."--Amazon.com